Urgensi Penegakan Kode Etik dalam Mencegah Mafia Peradilan - Asara Inacio Tae; Diana Nuri Yanti Kabu; Yafeti Waruwu; Sutiyani (AHKAM, 2026)
Although judicial corruption has received attention in various studies, research specifically examining the preventive (ex ante) function of enforcing legal professional codes of ethics remains limited. This study aims to analyze the urgency of enforcing legal professional codes of ethics as a preventive instrument for mitigating judicial corruption practices in Indonesia. The study employed a normative-qualitative legal method using a statutory approach and a conceptual approach, based on secondary legal materials purposively selected through a literature search. Data were collected through a document review of laws and regulations, the Surat Keputusan Bersama Mahkamah Agung dan Komisi Yudisial Nomor 047/KMA/SK/IV/2009–02/SKB/P.KY/IV/2009 tentang Kode Etik dan Pedoman Perilaku Hakim (KEPPH), and recent scholarly literature. The data were analyzed deductively and qualitatively using Lawrence M. Friedman’s Theory of Legal Effectiveness and Aristotle’s Theory of Virtue Ethics. The results indicate that judicial corruption practices primarily stem from a fragile legal culture and weak judicial accountability rather than merely from deficiencies in legal substance or structure. Firm and consistent enforcement of the KEPPH can narrow the gray areas of conduct that are not yet fully addressed by criminal law. These findings contribute to the development of legal effectiveness theory and virtue ethics-based professional ethics studies while broadening the understanding of preventive anticorruption strategies within the judiciary. This study concludes that consistent, collaborative, and transparent enforcement of the KEPPH by the Mahkamah Agung and Komisi Yudisial is an essential prerequisite for strengthening judicial integrity and restoring public trust. The practical implications of this study emphasize the need to strengthen the synergy between internal and external oversight by the Mahkamah Agung, Komisi Yudisial, and legal professional organizations. This study also opens opportunities for empirical research on the measurable impact of code-of-ethics enforcement on the prevalence of judicial corruption practices.